Hair testing for cocaine and metabolites by GC/MS: criteria to quantitatively assess cocaine use. Issue 8 (9th March 2012) - López‐Guarnido, O.; Álvarez, I.; Gil, F.; Rodrigo, L.; Cataño, H. C.; Bermejo, A. M.; Tabernero, M. J.; Pla, A.; Hernández, A. F.
ABSTRACT A simple, rapid and sensitive method has been developed and validated for the determination of cocaine and its main metabolites (benzoylecgonine and cocaethylene) in human hair. The method involved solid‐phase extraction with an Oasis HLB extraction cartridge and subsequent analysis by GC/MS. The limit of detection was 0.01 ng mg−1 for cocaine, 0.04 for benzoylecgonine and 0.03 for cocaethylene. The method validation included linearity (with a correlation coefficient >0.99 over the range 0.2–50 ng mg−1), intra‐ and inter‐day precision (always lower than 12%) and accuracy (mean relative error always below 17%) to meet the bioanalytical acceptance criteria. The procedure was further applied to 40 hair samples from self‐reported cocaine users arrested by the police who provided a positive urine‐analysis for cocaine, and was demonstrated to be suitable for its application in forensic toxicology. New approaches were raised to detect false‐negative results that allow a better interpretation of hair testing results. Copyright © 2012 John Wiley & Sons, Ltd.